Standards for determining the quality of online MBA education: a survey of accredited programmes. (22nd November 2004) - Haugen, Susan; Becker, D'Arcy; Erffmeyer, Robert
Students wishing to enroll in an online MBA programme have a wealth of information available via the internet. While there are many choices of programmes at every cost level, few standards have been established to allow programme comparisons. Because standards are not applied and/or reported by the individual institutions, there is no universal standard set of criteria by which students may judge online MBA programme quality. This paper discusses variables related to programme quality in the areas of institutional commitment and student services. We report data from online programmes meeting the initial quality standards of the Association to Advance Collegiate Schools of Business (AACSB), a national accrediting body for MBA programmes. Only 15% (5 of 33) of the accredited online MBA programmes examined here meet all 12 quality indicators. Results of analysis of the variables by cost quartile show that even the highest cost MBA programmes fail to meet many of these quality indicators.